Leishmania major Promastigotes Evade LC3-Associated Phagocytosis through the Action of GP63 - Matte, Christine (PLoS Pathog, 2016)
The protozoan Leishmania parasitizes macrophages and evades the microbicidal consequences of phagocytosis through the inhibition of phagolysosome biogenesis. In this study, we investigated the impact of this parasite on LC3-associated phagocytosis, a non-canonical autophagic process that enhances phagosome maturation and functions. We show that whereas internalization of L. major promastigotes by macrophages promoted LC3 lipidation, recruitment of LC3 to phagosomes was inhibited through the action of the parasite surface metalloprotease GP63. Reactive oxygen species generated by the NOX2 NADPH oxidase are necessary for LC3-associated phagocytosis. We found that L. major promastigotes prevented, in a GP63-dependent manner, the recruitment of NOX2 to phagosomes through a mechanism that does not involve NOX2 cleavage. Moreover, we found that the SNARE protein VAMP8, which regulates phagosomal assembly of the NADPH oxidase NOX2, was down-modulated by GP63. In the absence of VAMP8, recruitment of LC3 to phagosomes containing GP63-deficient parasites was inhibited, indicating that VAMP8 is involved in the phagosomal recruitment of LC3. These findings reveal a role for VAMP8 in LC3-associated phagocytosis and highlight a novel mechanism exploited by L. major promastigotes to interfere with the host antimicrobial machinery.